Ethnomusicology, Fieldwork, and the Refugee Experience - Marko Kölbl (Music & Minorities)
In this article, I discuss ethnomusicological takes on refugees and forced migration relating to five years of fieldwork within the Afghan community in Vienna. Against the background of the recent surge in ethnomusicological studies on forced migration, I critically interrogate my own positionality in relation to the coloniality of asylum that inherently racializes relations between researchers and refugees in ethnographic work. I then review narratives of “crises” and effects of “borders” in relation to migration between Afghanistan and Europe, specifically Austria.